2019
DOI: 10.1016/j.insmatheco.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

How can a cause-of-death reduction be compensated for by the population heterogeneity? A dynamic approach

Abstract: A growing number of studies indicate a widening of socioeconomic inequalities in mortality over the past decades. It has therefore become crucially important to understand the impact of heterogeneity and its evolution on the future mortality of heterogeneous populations. In particular, recent developments in multi-population mortality have raised a number of questions, among which is the issue of evaluating cause-of-death reduction targets set by national and international institutions in the presence of heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Our goal is to study, in a simplified model, the impact of a mortality shock in the population, for instance due to an epidemic outbreak, when the shock not only impact individuals' longevity, but also the population composition through swap events ( [Kaakai et al, 2019]). Swap events can provide a way to model compositional changes induced by public measures or variations in the general quality of life.…”
Section: Stochastic Differential Equation Driven By Extended Poisson ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our goal is to study, in a simplified model, the impact of a mortality shock in the population, for instance due to an epidemic outbreak, when the shock not only impact individuals' longevity, but also the population composition through swap events ( [Kaakai et al, 2019]). Swap events can provide a way to model compositional changes induced by public measures or variations in the general quality of life.…”
Section: Stochastic Differential Equation Driven By Extended Poisson ...mentioning
confidence: 99%
“…However, this is not consistent with the demographic rates. Indeed, there should naturally be more individual in the less deprived Subgroup 1 in older age classes, due to mortality differences between the subgroup, which is reflected by the subgroups' age pyramids (see [Kaakai et al, 2019] for more details).…”
Section: Model Without Swap Eventsmentioning
confidence: 99%
“…We develop a continuous deterministic framework. It is common in the population dynamics literature to study deterministic models as they can be viewed as limit models when the size of the population becomes very large (Kaakai et al, 2018;Attias et al, 2016). 5 Furthermore, continuous frameworks also improve traceability of the results (Bommier and Lee, 2003).…”
Section: Population Dynamicsmentioning
confidence: 99%
“…Systematic mortality improvement trends vary with the risk characteristics of individuals in a population (including by age and gender) and this variation determines the degree of mortality heterogeneity within a population [Vaupel et al (1979), Meyricke and Sherris (2013)]. Further, some authors have shown that population heterogeneity can impact population dynamics and aggregate mortality trends [Kaakai et al (2019)] Our paper relies on the assumption that mortality improvement trends differ due to different health status across individuals with the same age and gender, based on evidence that health status (especially chronic illness) is significantly correlated with disability [Sherris and Wei (2021)] and mortality [Brown and Warshawsky (2013), Koijen et al (2016), Yogo (2016)].…”
Section: Introductionmentioning
confidence: 99%